2022
DOI: 10.5334/joc.234
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Binding and Retrieval in Sequences of Discrete Movements – Evidence from Grasping Actions

Abstract: In everyday life humans are confronted with changing environmental demands. In order to act successfully and achieve intended goals, action control is required. A recent approach, the Binding and Retrieval in Action Control (BRAC) framework, attempts to provide an overarching perspective on action control. Based on basic principles such as binding and retrieval, findings from several experimental paradigms could be integrated. However, the focus so far has been on rather artificial paradigms involving very sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…However, when object properties change continuously, predictions are less reliable and can be misleading. Yet, even in such cases, humans plan their movements assuming that the object in question has the same properties as those experienced in the previous trial 24 , 25 , 32 . Our experiments support such predictive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, when object properties change continuously, predictions are less reliable and can be misleading. Yet, even in such cases, humans plan their movements assuming that the object in question has the same properties as those experienced in the previous trial 24 , 25 , 32 . Our experiments support such predictive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, when object properties change continuously, predictions are less reliable and can be misleading. Yet, even in such cases, humans plan their movements assuming that the object in question has the same properties as those experienced in the previous trial (Beyvers et al, 2022b; Lukos et al, 2013; Witney et al, 2001). Our experiments support such predictive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…However, grouping of visual effects did not impact on the size of response-response binding effects. Beyvers and colleagues ( 2022 ) assessed the impact of grouping by task instructions on complex grasping responses – they found that when features like mass distribution or position repeated from prime to probe grasping movements were more accurate and stable. These findings broaden the scope of BRAC to grasping responses.…”
mentioning
confidence: 99%